Fundraising organisations for Basque children and Spanish refugees - National Joint Committee for Spanish Relief (1940)
1940 038-0040-004 -2- Details of Correspondence Scheme Partly as a result of the work of the British Committee for Refugees from Spain, many Spaniards in France have a very strong feeling of friendship for English people, and a desire to learn more about this country. It is probably equally true that many English people, who have become deeply interested in Spain as a result of the magnificent struggle of the Republicans, would be glad of the opportunity to be in direct personal touch with these Spaniards, Our office at Perpignan has received numerous requests from Spaniards to be given the names of English people with whom they might correspond. The language question presents a difficulty, but we think it could be overcome by a regular system of translation carried out by Spaniards in London, provided that sufficient people are interested to make it worthwhile. Many of these refugees are now in work gangs or in the Foreign Legion, most are separated from their families and friends. They long for news from this country, they long to be able to tell an English friend of their present life and experiences. Send your name and address to the British Committee for Refugees from Spain, and a note as to the kind of person to whom you would like to write. For example, a worker, a technician, a musician or a professor, an International Brigader and so forth. We will do our best to help you in your choice. N.B. LABOUR An alien may be granted permission to work in this country at the discretion of the Labour Exchange manager, provided that no British labour is obtainable, that they receive the normal wage, and their employment has the approval of the Trade Union. NATIONAL JOINT COMMITTEE FOR SPANISH RELIEF 30, Eccleston Street London, S.W.1. 292/946/38/40(IV)